Interaction of cultural and professional values: Case studies of Arab social work students - Jammal Abboud, Romain; Sowan, Wafaa; Al Krenawi, Alean (Journal of International Students, 2026)
This study examined the cultural and professional values of social work students from collectivist and patriarchal backgrounds who were educated in Western-oriented academic settings. Minority students in international learning environments often experience tension when liberal professional values, such as autonomy and gender equality, conflict with cultural norms that prioritize family honor, social cohesion, and deference to authority. Using a qualitative case study approach, this research analyzed two cases of female students who encountered value-related dilemmas during their field education. Thematic analysis of supervision transcripts, reflective journals, and field reports revealed three central themes: emotional strain resulting from internal value dissonance, the ongoing negotiation of cultural and professional identities, and the significant role of supervision in linking cultural belonging with ethical professional practice. Based on the findings, a four-stage culturally responsive supervision model was developed to guide educators and institutions in creating inclusive, equitable, and culturally informed learning environments for diverse student populations.